KAJIAN DEBIT BANJIR AKIBAT PERUBAHAN PENGGUNAAN LAHAN DI SUB DAS BELIK, DAERAH ISTIMEWA YOGYAKARTA - , NOVIANA DIAN UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Belik sub-watershed is a catchment area that located in urban area of Yogyakarta regency and Sleman regency. Flood is often occur in that area when the rainy season because of development of impermeable land, so that increasing the runoff coefficient. Because of that, this research have purpose to study land use change spatially and temporally on the year of 2003 and 2012, to calculate flood discharge in study area with various return period connected with river capacity, and to analyze influence of land use change to flood discharge in study area. Interpretation method of satellite imagery is used to know land use on 2003 whereas field check according to interpretation result is used to know land use on 2012. Land use change can be known using overlay method both of the map on that year. Frequency analysis with return period of 2, 5, 10, and 20 years and Mononobe formula are used to calculate rain intensity whereas flood discharge is calculated using rational method. River capacity is calculated using slope-area method to know that flood discharge can be accommodated or not. The result of this research show that the most decreasing land use areal is area with vegetation which is 23,47 Ha (3,44 %) whereas the most increasing land use areal is real estate areas which is 22,86 Ha (3,34 %). Flood discharge increase from year 2003 to year 2012 in all of catchment area. River capacity of Karangwuni, Klebengan, Lembah, and Klitren catchment area cannot accommodate that discharge whereas river capacity of main catchment area is 36,07 m3/s can accommodate discharge with return period of 2 years. The increasing of runoff coefficient average in study area is 5,17 % - 16,28 % because of land use change to impermeable land so that increase flood discharge. Flood discharge that cannot be accommodated by the river causes flood and puddle in study area during rainy season.